1975
DOI: 10.1002/pol.1975.180131212
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nucleation of crystallization of high polymers from the melt. II. Aspects of transcrystallinity and nucleation density

Abstract: SynopsisIn the initial stage of the development of transcrystallinity, nuclei appear sporadically on the substrate. The growth rate and melting temperature of the transcrystalline region are found to be the same as those of spherulites nucleated in the bulk of the polymer. Nucleation densities n, a t the interface, and nb in bulk, for the crystallization of isotactic polypropylene, poly (ethylene oxide), and poly (butene-1) in contact with various substrates, have been measured by counting the number of spheru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 4 publications
3
18
0
Order By: Relevance
“…Reinforcement with each of the above materials increases the starting crystallization temperature [13][14][15][16][17] and induces a shorter processing time in injection molding [18], and consequently affects the percentage of crystallinity of the composite. The studies have revealed that bulk crystallinity is increased over that of non-reinforced polymer because of enhanced nucleation in the presence of mineral reinforcement [13][14][15]19]. Atomic force microscopy suggested that in wollastonite-polypropylene systems, the lamellae were more closely packed in the vicinity of the particle-matrix as compared to regions far away [13,14].…”
Section: Introductionmentioning
confidence: 95%
“…Reinforcement with each of the above materials increases the starting crystallization temperature [13][14][15][16][17] and induces a shorter processing time in injection molding [18], and consequently affects the percentage of crystallinity of the composite. The studies have revealed that bulk crystallinity is increased over that of non-reinforced polymer because of enhanced nucleation in the presence of mineral reinforcement [13][14][15]19]. Atomic force microscopy suggested that in wollastonite-polypropylene systems, the lamellae were more closely packed in the vicinity of the particle-matrix as compared to regions far away [13,14].…”
Section: Introductionmentioning
confidence: 95%
“…Epitaxial crystallization and thin-film epitaxial processes have also been used as a method of orienting macromolecules onto inorganic substrate surfaces to study polymer extended-chain conformation. [4,9,10] Heterogeneously nucleated crystal growth and epitaxy has been studied for several flexible polymer systems including isotactic poly(propylene), [11,12] poly(butene-1), polycaprolactone, [3,13,14] poly(propylene), [11] and polyethylene. [15,16] Due to an epitaxial interaction between poly-(propylene) and graphite, transcrystalline growth was observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, lignocellulosic materials were not investigated. Frequently, the nucleation phenomenon is closely correlated with the phenomenon of epitaxy as evidenced by the pioneering studies of Chatterjee et al [12][13][14]. Investigations on the effect of talc used not only as filler but, primarily, as a nucleant of the crystallisation process were carried out by Mencel and Varga [15].…”
Section: Introductionmentioning
confidence: 99%